Effect of supplementation with barley and calcium hydroxide on intake of Mediterranean shrubs - Dragan Skobic; Slaven Zjalic; Svjetlana Stanic; Nevenko Herceg; Jozo Rogosic; Tomislav Saric (Italian Journal of Animal Science, 2011)
Maquis plant communities are one of the most varied vegetation types in the Mediterranean region and an important habitat for wild and domestic herbivores. Although the majority of these shrubs are nutritious, the secondary compounds are main impediments that reduce their forage value. In five experiments we determined the effect of supplementing goats with calcium hydroxide plus barley, and barley alone on intake of five dominant shrubs (Quercus ilex, Erica multiflora, Arbutus unedo, Viburnum tinus and Pistacia lentiscus) of the Mediterranean maquis community. The combination of calcium hydroxide plus barley and barley alone increased utilization of all five investigated Mediterranean shrubs; therewith that intake of Arbutus unedo and Viburnum tinus was not statistically significant. Supplemented goats with calcium hydroxide plus barley or barley alone could be effective in controlling secondary compounds-rich Mediterranean shrubs where their abundance threatens biodiversity. This control can be facilitated by browsing dominant Mediterranean shrubs, which has been shown to be effective in managing Mediterranean maquis density. Calcium hydroxide and barley (energy) enhance use of secondary compounds-containing plants, which may increase production of alternate forages and create a more diverse mix of plant species in the Mediterranean maquis plant community.